Childfree dalam Keluarga Muslim : Analisis Maqasid Syariah di Kota Pekanbaru - Muhammad Zirzis Zein; Fauzi Ardian (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study aims to analyze the phenomenon of childfree within Muslim families in Pekanbaru City from the perspective of maqasid al-shari‘ah. This research employs a qualitative method with a case study approach, utilizing interviews, observations, and documentation involving five informants selected through purposive sampling. The findings reveal that the decision to remain childfree is influenced by mental readiness, economic conditions, and social considerations, and is made through mutual agreement between spouses in a conscious manner. From the perspective of maqasid al-shari‘ah, having offspring is an important objective of marriage; however, childfree falls within the domain of ijtihadiyah and can be understood through the concept of maslahah mursalah. As long as it is based on public benefit, such as the protection of life and wealth, this decision can be considered permissible (mubah). Therefore, the childfree phenomenon is not entirely contradictory to the objectives of Islamic law, provided it is grounded in rational considerations and public benefit.